Overseas contacts, conception to completion proceedings of the conference held in London, 14-15 November 1979. (Institution of Civil Engineers, 1980)
H.R.H. The Duke of Gloucester provides the opening address for these papers which cover getting work overseas for a consulting engineer, highlights the market, focuses on British Rail abroad, and discusses contracts, local associates and joint ventures.